A Mathematical Model for Swallowing of Concentrated Fluids in Oesophagus - S. K. Pandey; Dharmendra Tripathi (Applied Bionics and Biomechanics)
This model investigates particularly the impact of an integral and a non-integral number of waves on the swallowing of food stuff such as jelly, tomato puree, soup, concentrated fruits juices and honey transported peristaltically through the oesophagus. The fluid is considered as a Casson fluid. Emphasis is on the study of the dependence of local pressure distribution on space and time. Mechanical efficiency, reflux limit and trapping are also discussed. The effect of Casson fluid vis-à-vis Newtonian fluid is investigated analytically and numerically too. The result is physically interpreted as that the oesophagus makes more efforts to swallow fluids with higher concentration. It is observed that the pressure is uniformly distributed when an integral number of waves is there in the oesophagus; but it is non-uniform when a non-integral number of waves is present therein. It is further observed that as the plug flow region widens, the pressure difference increases, which indicates that the averaged flow rate will reduce for a Casson fluid. It is also concluded that Casson fluids are more prone to reflux.